Reducing sedentary time and fat mass may improve glucose tolerance and insulin sensitivity in adults surviving 6 months after stroke: A phase I pilot study. (June 2017) - Borschmann, Karen N; Ekinci, Elif I; Iuliano, Sandra; Churilov, Leonid; Pang, Marco YC; Bernhardt, Julie
Introduction: Deranged glycaemic control is common post-stroke, increasing risks of recurrent stroke and development of diabetes. The aim of the study is to examine glucose metabolism in relation to body composition, physical activity and sedentary time post-stroke. Patients and methods: Observational study: Non-diabetic adults, unable to walk independently, were recruited within 2 weeks of first stroke. Primary outcome: 2-h glucose level (mmol/l, oral glucose tolerance test), assessed at baseline and 6 months. Homeostasis Model Assessment of Insulin Sensitivity, total body fat and lean mass (dual energy X-ray absorptiometry), sedentary time (lying or sitting), standing and walking (PAL2 accelerometer) were assessed at baseline, 1, 3 and 6 months. Generalised estimating equations were used to examine change over time and associations between outcome measures. Results: Thirty-six participants (69.5 years (standard deviation 11.7), 13 (36.1%) female, moderate stroke severity (National Institute of Health Stroke Scale 11.5 (interquartile range 9.75, 16)). Within 6 months, adjusting for age and National Institute of Health Stroke Scale, every month 2-h glucose reduced by 4.5% ( p  < 0.001), Homeostasis Model Assessment of Insulin Sensitivity improved 3% ( p =  0.04) and fat mass decreased 490 g (95% confidence interval 325, 655; p  = 0.01). For every extra kilogram of body fat, 2-h glucose increased by 1.02 mmol/L (95% confidence interval 1.01, 1.02; p  = 0.001); Homeostasis Model Assessment of Insulin Sensitivity reduced by 0.98% (95% confidence interval 0.97, 0.99; p  = 0.001). Time spent sedentary reduced from 98.5% of measurement period (interquartile range 94.3, 99.8) to 74.3% (interquartile range 65.5, 88.6), by 2.8% monthly (95% confidence interval 1.8, 3.9, p  < 0.001). For every additional 5% sedentary time, 2-h glucose increased by 1.05 mmol/L (95% confidence interval 1.04, 1.07; p  < 0.001). Conclusion: Reducing sedentary time and fat mass within 6 months of stroke may improve glucose tolerance and insulin resistance.